Ethylene, a key factor in the regulation of seed dormancy - Corbineau, Françoise; Xia, Qiong; Bailly, Christophe; El-Maarouf-Bouteau, Hayat (Frontiers in Plant Science, 2014)
Ethylene is an important component of the gaseous environment, and regulates numerous plant developmental processes including seed germination and seedling establishment. Dormancy, the inability to germinate in apparently favorable conditions, has been demonstrated to be regulated by the hormonal balance between abscisic acid (ABA) and gibberellins (GAs). Ethylene plays a key role in dormancy release in numerous species, the effective concentrations allowing the germination of dormant seeds ranging between 0.1 and 200 μL L-1. Studies using inhibitors of ethylene biosynthesis or of ethylene action and analysis of mutant lines altered in genes involved in the ethylene signaling pathway (etr1, ein2, ain1, etr1, and erf1) demonstrate the involvement of ethylene in the regulation of germination and dormancy. Ethylene counteracts ABA effects through a regulation of ABA metabolism and signaling pathways. Moreover, ethylene insensitive mutants in Arabidopsis are more sensitive to ABA and the seeds are more dormant. Numerous data also show an interaction between ABA, GAs and ethylene metabolism and signaling pathways. It has been increasingly demonstrated that reactive oxygen species (ROS) may play a significant role in the regulation of seed germination interacting with hormonal signaling pathways. In the present review the responsiveness of seeds to ethylene will be described, and the key role of ethylene in the regulation of seed dormancy via a cross-talk between hormones and other signals will be discussed.